The SESAME/CASSE instrument listening to the MUPUS PEN insertion phase on comet 67P/Churyumov–Gerasimenko. (August 2016) - Knapmeyer, M.; Fischer, H.-H.; Knollenberg, J.; Seidensticker, K.J.; Thiel, K.; Arnold, W.; Schmidt, W.; Faber, C.; Finke, F.; Möhlmann, D.
Abstract: After the final landing of Philae at the Abydos site on comet 67/P Churyumov–Gerasimenko, the MUPUS (Multipurpose Sensors for Surface and Sub-Surface Science) device started hammering itself into the cometary ground on 14th November 2014, and continued hammering for more than 3 h. During this period, the CASSE (Comet Acoustic Surface Sounding Experiment) instrument, part of SESAME (Surface Electric Sounding and Acoustic Monitoring Experiment), was listening to the hammer strokes of MUPUS, which was the strongest available source for a seismic–acoustic experiment to determine mechanical properties of the ground. All sensors survived the multiple touchdowns of Philae undamaged and provided recordings of 14 hammer strokes at audible frequencies. The data suggests that Philae was slightly rocking or swinging during the initial phase of the experiment, finally finding an attitude that not only stopped this motion but also improved the coupling of sensors to the ground and thus the recordings. The experiment provides several lessons that might be useful for the development of similar experiments on future spacecraft. The most serious issues concerning the CASSE recordings are clock accuracy and synchronicity and the timing of the source. Future designs may want to consider additional sensors in close proximity to the source, and direct communication between experiments to overcome this. The present design allows the evaluation of arrival time differences only, rather than absolute travel times. In this contribution, we focus on the technical and operational aspects of this experiment. A scientific evaluation of the data received will follow in a second paper. Highlights: MUPUS attempted to hammer its thermal probe into the cometary ground of Abydos. Three triaxial accelerometers in Philae's landing feet were listening. We describe experiment setup and operation. Sound was transmitted through the comet. All feet have mechanical connection to the ground, improving during the experiment.